Molecular Distillation of Lavender Supercritical Extracts: Physicochemical and Antimicrobial Characterization of Feedstocks and Assessment of Distillates Enriched with Oxygenated Fragrance Components - Agnieszka Dębczak; Katarzyna Tyśkiewicz; Zygmunt Fekner; Piotr Kamiński; Grzegorz Florkowski; Marcin Konkol; Edward Rój; Agnieszka Grzegorczyk; Anna Malm (Molecules, 2022)
Lavandula angustifolia is one of the most widely cultivated non-food crops used in the production of essential oil; it is used in perfumery, aromatherapy, pharmaceutical preparations, and food ingredients. In this study, supercritical fluid extraction (SFE) and molecular distillation (MD) were combined, primarily to enrich scCO2 extracts with lavender oxygenated monoterpenes, avoiding thermal degradation, hydrolysis, and solvent contamination, and maintaining the natural characteristics of the obtained oils. Molecular distillation was developed for the first time for the extraction of crucial lavender fragrance ingredients, i.e., from two scCO2 extracts obtained from dry flower stems of lavender cultivated in Poland and Bulgaria. The best results for high-quality distillates were obtained at 85 °C (EVT) and confirmed that linalyl acetate content increased from 51.54 mg/g (initial Bulgarian lavender extract, L-Bg-E) and 89.53 mg/g (initial Polish lavender extract, L-Pl-E) to 118.41 and 185.42 mg/g, respectively, corresponding to increases of 2.3 and 2.1 times in both distillate streams, respectively. The distillates, light oils, and extracts from lavender were also evaluated for their antimicrobial properties by determining the minimum inhibitory concentration (MIC) by the broth microdilution method. Generally, Gram-positive bacteria and Candida spp. were more sensitive to all distilled fractions and extracts than Escherichia coli (Gram-negative bacteria).